Book Review: Mauro Carbone and Graziano Lingua, Toward an Anthropology of Screens. Showing and Hiding, Exposing and Protecting - Andrea Zoppis (Technophany)
In this text I offer a review of the book ‘Toward an Anthropology of Screens’ by Mauro Carbone and Graziano Lingua. After briefly introducing the operation proposed by the authors, I consider the salient points of the work. Finally, I propose an assessment of the relevance of the book in contemporary philosophical debate.